Different Types of the Complications Associated with Induced Abortion and to Determine the Relative Frequencies (Journal of Fatima Jinnah Medical University, 2018)
Objective: To find out different types of complications associated with induced abortion and to determine the relative frequencies.Study Design: Descriptive study.Place and duration: This study was carried out in Gynecology Deptt. Lady Aitcheson Hospital, from 16th December 2010 to 15th March 2011.Patients and Methods: The study was conducted three months from 16th December 2010 to 15th March 2011 in Gynecology Deptt Lady Aitcheson Hospital. A total of 30 patients presented with the history of induced abortion were included in the study. Special proforma was designed to collect the data.Conclusion: In conclusion, septic induced abortion is associated with serious complications, which need expensive treatments, increasing economic burden and work load, and above all patients suffering. As it is a preventable condition we suggest commitment to health education, family planning promotion and bringing down the rates of unsafe abortions as solution to the problem.
Keywords: Septic induced abortion, complications, and relative frequencies.